2023
DOI: 10.14245/ns.2245042.521
|View full text |Cite
|
Sign up to set email alerts
|

A 30-Year Worldwide Research Productivity of Scientific Publication in Full-Endoscopic Decompression Spine Surgery: Quantitative and Qualitative Analysis

Abstract: Objective: The ever-growing number of articles related to full-endoscopic spine surgery published in the last few decades presents a challenge which is perplexing and time-consuming in identifying the current research status. The study aims to identify and analyze the most cited works related to full-endoscopic decompression spine surgery, compare the articles published by different publishers and area, and show the current publication status of full-endoscopic research.Methods: Using Bibliometrix, CiteSpace, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…A study conducted by Liu et al 31 shows that while the number of publications on endoscopy research continues to increase, the citation rate of endoscopy-related papers has declined over the past 30 years. More guidelines for developing standards have been published, indicating the gradual maturity of total endoscopic spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Liu et al 31 shows that while the number of publications on endoscopy research continues to increase, the citation rate of endoscopy-related papers has declined over the past 30 years. More guidelines for developing standards have been published, indicating the gradual maturity of total endoscopic spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5,56 These focused analyses have allowed for a more granular dissection of various topics within the field of spine research, which would have been challenging with our larger data set. Similarly, bibliometric studies on the application of 3D printing in spine surgery, 32 intraoperative neuromonitoring, 27 endoscopic approaches, 13,17,20,26 and robotics 29 have provided valuable insights into the most productive institutions, countries, and journals, as well as the hotspots in each area.…”
Section: Discussionmentioning
confidence: 99%
“…Since open surgery was first applied to LDH treatment in 1934, multiple surgical techniques ranging from microdiscectomy (MD) to microendoscopic discectomy have been developed. The emergence of visual endoscopic technology has led to the development of transforaminal endoscopic lumbar discectomy (TELD), which is now gaining popularity as a treatment option [ 2 , 3 ]. Several studies have confirmed the excellent short-term clinical efficacy of TELD, and it is considered a treatment of choice for LDH because of its unique advantages of smaller incisions, decreased damage to soft tissues, and faster postoperative recovery [ 4 - 8 ].…”
Section: Introductionmentioning
confidence: 99%